Design of Ratiometric Fluorescent Probes Based on Arene–Metal‐Ion Interactions and Their Application to CdII and Hydrogen Sulfide Imaging in Living Cells. Issue 8 (23rd January 2014) - Takashima, Ippei; Kinoshita, Miyuki; Kawagoe, Ryosuke; Nakagawa, Saika; Sugimoto, Manabu; Hamachi, Itaru; Ojida, Akio
Abstract Non‐coordinative interactions between a metal ion and the aromatic ring of a fluorophore can act as a versatile sensing mechanism for the detection of metal ions with a large emission change of fluorophores. We report the design of fluorescent probes based on arene–metal‐ion interactions and their biological applications. This study found that various probes having different fluorophores and metal binding units displayed significant emission redshift upon complexation with metal ions, such as AgI, CdII, HgII, and PbII. X‐ray crystallography of the complexes confirmed that the metal ions were held in close proximity to the fluorophore to form an arene–metal‐ion interaction. Electronic structure calculations based on TDDFT offered a theoretical basis for the sensing mechanism, thus showing that metal ions electrostatically modulate the energy levels of the molecular orbitals of the fluorophore. A fluorescent probe was successfully applied to the ratiometric detection of the uptake of CdII ions and hydrogen sulfide (H2S) in living cells. These results highlight the utility of interactions between arene groups and metal ions in biological analyses.